2007
DOI: 10.1021/bm0700892
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Life Cycle Studies on Poly(3-hydroxybutyrate)-Based Composites as Potential Replacement for Conventional Petrochemical Plastics

Abstract: A cradle-to-grave environmental life cycle assessment (LCA) of a few poly(3-hydroxybutyrate) (PHB) based composites has been performed and was compared to commodity petrochemical polymers. The end products studied are a cathode ray tube (CRT) monitor housing (conventionally produced from high-impact polystyrene, HIPS) and the internal panels of an average car (conventionally produced from glass-fibers-filled polypropylene, PP-GF). The environmental impact is evaluated on the basis of nonrenewable energy use (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 37 publications
2
78
0
Order By: Relevance
“…Conversely, in a plastic bottle case study, Rebitzer et al (2002) concluded that corn-based PHB caused higher environmental impacts than its petrochemical counterparts due to corn-glucose production and heating requirements. Rebitzer et al's (2002) results have been supported by Pietrini et al (2007) who also pointed out that expanding the system boundary from factory gate to grave led to PHB having a higher impact than PP even though on per kg of polymer (cradle-to-gate) basis PHB had a lower impact than PP.…”
Section: Lca Of Light-weight Eco-compositesmentioning
confidence: 82%
“…Conversely, in a plastic bottle case study, Rebitzer et al (2002) concluded that corn-based PHB caused higher environmental impacts than its petrochemical counterparts due to corn-glucose production and heating requirements. Rebitzer et al's (2002) results have been supported by Pietrini et al (2007) who also pointed out that expanding the system boundary from factory gate to grave led to PHB having a higher impact than PP even though on per kg of polymer (cradle-to-gate) basis PHB had a lower impact than PP.…”
Section: Lca Of Light-weight Eco-compositesmentioning
confidence: 82%
“…Bio-based or biodegradable polymers have the potential to replace conventional petrochemical plastics [27], high-strength polymer nanocomposites can replace steel, aluminum, or other metals in industrial applications [25,26] and also, they can be used in the production of alternative fuel cells [29]. Results obtained from the reviewed studies vary in terms of carbon emissions of nanomaterial-based polymers compared to alternative technologies.…”
Section: Polymer Sectormentioning
confidence: 99%
“…In the study of Hervy et al [26], application of nanofibrillated cellulose reinforced epoxy composites as applied in vehicle body panels resulted in almost breakeven of carbon emissions compared to neat polylactide (PLA) and glass fiber/polypropylene (GF/PP) alternatives. In the study of Pietrini et al [27] the use of nanoscaled organophilic montmorillonite PHBs (poly3-hydroxybutyrate) resulted in a better carbon impact in the case of CRT monitors (using HIPS) and in a comparable carbon impact in the case of car body panels (using GF-PP). In the study of Notter et al [29], multiwalled carbon nanotubes are used in the production of polymer electrolyte membrane fuel cells (PEM FCs).…”
Section: Polymer Sectormentioning
confidence: 99%
See 2 more Smart Citations